NILAI-NILAI PANCASILA DALAM PERSPEKTIF AKHLAK ISLAM TERHADAP PENGUATAN PENDIDIKAN KARAKTER DAN KEPEMIMPINAN - Akmir Akmir; Cahaya Wulandari; Nabila Fiqriyah; Niken Novitasari; Nuraisyah Nuraisyah; Resky Amri (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study analyzes the integration of Islamic values and Pancasila in shaping the character and leadership of the younger generation through education in Indonesia. Various studies indicate that Islam and Pancasila share conceptual alignment in aspects of leadership, social justice, deliberation, tolerance, and humanitarian ethics, which are relevant to strengthening character education. The concept of qawwam in Tafsir al Manar, which emphasizes trustworthiness, justice, moral responsibility, and deliberation, is proven to be relevant to modern educational governance, particularly in fostering educational leadership that is integrity driven and oriented toward public benefit. Meanwhile, the fourth and fifth principles of Pancasila demonstrate theological compatibility with the principles of shura and social justice in Islam, thereby reinforcing democratic practices within educational environments and participatory learning processes. In the context of the younger generation, the integration of Islamic Religious Education and Pancasila Education becomes a strategic approach to addressing the challenges of globalization, digitalization, and moral degradation. These subjects contribute to shaping students who are religious, moderate, tolerant, nationalistic, and resilient in character. Furthermore, the principles of justice and deliberation in Islam provide an ethical foundation for developing a humane and equitable school culture. The findings affirm that the synergy between Islamic values and Pancasila serves as a strategic foundation for strengthening character education and cultivating a civilized generation capable of responding to contemporary challenges. ABSTRAK Penelitian ini menganalisis integrasi nilai nilai Islam dan Pancasila dalam membentuk karakter dan kepemimpinan generasi muda melalui pendidikan di Indonesia. Berbagai kajian menunjukkan bahwa Islam dan Pancasila memiliki keselarasan konseptual dalam aspek kepemimpinan, keadilan sosial, musyawarah, toleransi, dan etika kemanusiaan yang relevan bagi penguatan pendidikan karakter. Konsep qawwam dalam Tafsir al-Manar yang menekankan amanah, keadilan, tanggung jawab moral, dan musyawarah terbukti relevan bagi tata kelola pendidikan modern, khususnya dalam membangun kepemimpinan pendidikan yang berintegritas dan berorientasi pada kemaslahatan. Sementara itu, sila keempat dan kelima Pancasila memiliki kesesuaian teologis dengan prinsip syura dan keadilan sosial dalam Islam, sehingga dapat memperkuat praktik demokrasi dalam lingkungan pendidikan dan pembelajaran yang partisipatif. Dalam konteks generasi muda, integrasi Pendidikan Agama Islam dan Pendidikan Pancasila menjadi strategi penting dalam menghadapi tantangan globalisasi, digitalisasi, dan degradasi moral. Kedua mata pelajaran tersebut berperan dalam membentuk peserta didik yang religius, moderat, toleran, nasionalis, serta memiliki ketangguhan karakter. Selain itu, prinsip keadilan dan musyawarah dalam Islam memberikan dasar etis bagi pengembangan budaya sekolah yang humanis dan berkeadilan. Temuan ini menegaskan bahwa sinergi nilai Islam dan Pancasila merupakan fondasi strategis dalam memperkuat pendidikan karakter dan membangun generasi berkeadaban yang mampu menjawab tantangan zaman.